(untitled) (Research, Society and Development, 2021)
The objective of the study was to establish the profile of feminicide in the state of Sergipe from 2016 to 2019. A cohort, descriptive, exploratory study was carried out, with a quantitative approach, through data collection, with a population of women over 18 years, victims of femicide. During the study period there were 262 violent deaths of women, 70 of these deaths were characterized as femicides, whose rate of femicide per 100 thousand women ranged from 1.51 to 2.61. There were 44.3% of femicides in the metropolitan region and 55.7% in other municipalities in the state. In all the correlations between the variables, the use of firearms prevailed as the causative agent of death. Likewise, the residence prevailed as the place of occurrence of femicide. The frequency of color / brown race was higher in the metropolitan region in relation to the other municipalities. The presence of economically active women was statistically significant. hen this variable was related to color / race, this presence was more expressive among white women. Regarding education, the occurrence of incomplete elementary education predominated in all situations. At the Sergipe Court of Justice, of the 31 investigative procedures initiated, 25 were of femicides, demanded by 14 of the 40 counties in the state of Sergipe. Feminicide was evidenced in this study as the main cause of violence in young adult women, thus characterizing an epidemiological phenomenon that has been spreading not only in Brazil, but throughout the world.